Fixation of Proximal Third Humeral Shaft Fractures in Older Patients - Jared Quarcoopome MBBS; John Adam MBBS; Bence Baljer MBBS; Ahmed Nagi MBChB; Will Eardley MBChB, MSc; James L. McVie MBBS (Geriatric Orthopaedic Surgery & Rehabilitation, 2023)
Background Humeral shaft fractures occur frequently in older patients. The more proximal end of the shaft is prone to non-union when compared with more distal fractures. We provide an overview of several key features of this significant patient group. Method Our institutional fracture database was searched for all cases of proximal third humeral shaft fractures in patients over 60 years of age. Retrospective evaluation of patient demographics, management, length of stay and incidence of non-union was performed. Results 75 patients (61 female) were analysed. 33 patients were ‘frail’ (Clinical Frailty Scores of >4). Non-union occurred in 19 of 45 non-surgically treated fractures and in 1 of 37 cases treated surgically. Mean length of stay was 5.9 days (non-operative) and 6.6 days (operative). Proximal extension into the humeral head is common. Conclusion Non-surgical management of proximal third humeral shaft fractures is associated with an increased risk of non-union. We detail an operative technique and case example supporting early fixation of displaced proximal third humeral shaft fractures in older patients that can be utilized for both primary and delayed fixation. In view of the significant association of non-union a well-constructed prospective cohort study with outcome assessment would be of value to further characterize this emerging injury population. Level of Evidence: Level IV, retrospective case series